A sustainable community based tourism enterprises through Amanah Ikhtiar Malaysia in Semporna, Sabah: opportunities and challenges - Ibrahim, Mohd Romzee; Shuib, Ahmad; Ramachandran, Sridar; Mohammad Afandi, Syamsul Herman (Institut Kajian Dasar Pertanian dan Makanan, Universiti Putra Malaysia, 2015)
The development of a sustainable community based tourism is determined on satisfying the objectives of all stakeholders in the system. The inter relationships among the stakeholders must be fully recognized since each stakeholder’s needs may be dissimilar from the others. The challenge for local communities and policy makers is to ascertain or generate opportunities that will provide sustainable development. Tourism is seen as one sector that could possibly provide such opportunities by the creation of tourism enterprises among local communities. Tourism enterprises are in most situations likely to be micro businesses. Most of the micro businesses ventured by local communities have relatively high failure rates. Therefore, it is important to deliberate a substantial integration among responsible stakeholders as to encourage and support tourism micro business ventures. This paper seeks to explore the opportunities and challenges of the community based tourism enterprises development in Semporna. The paper reports on panel data obtained from various local authorities, semi-structured interviews and author’s observations. The study highlights lack of participation in tourism micro etrprise among local communities and challenges faced by local authorities in supporting the ventures.